التصميم الانشائي لمستوصف في مدينة الخليل - العطاونة, أفنان; عصافرة, حلا (جامعة بوليتكنك فلسطين - مباني, 2021)
Structural design is one of the most important designs necessary for the building after the architectural design. Calculating the loads, designing the structural elements, and maintaining the safety and security of the building and the people are all the responsibility of the civil engineer. The idea of the project is summarized in the structural design of a proposed clinic to be designed in the city of Hebron. The architectural blocks in an aesthetic way that reflects the different function contained in the spaces of the building. This layout consists of three floors and contains stores for electrical tools, medicines, patients’ clinics, doctors’ rooms, premature babies’ rooms, x-rays, bathroom facilities for patients and administration rooms. The basement floor has an area of 640 square meters and consists of a water well, kitchen, electrical store, medicine store and laundry room The area of the ground floor is 945 square meters, which consists of the administration room with the secretariat, clinic rooms, emergency rooms, reception, laboratory, doctor's room, radiology room, and accounting room The area of the first floor is 932 square meters, which consists of rooms for doctors, women's rooms, rooms for premature babies, an operating room, a rehabilitation room, and accounting rooms
Keywords: التصاميم الانشائية; الابنية الصحية